63.3: Fabrication of 8k4k Organic EL Panel using High‐Mobility IGZO Material. Issue 1 (June 2015) - Okazaki, Kenichi; Kanemura, Hiroshi; Kurosaki, Daisuke; Shima, Yukinori; Koezuka, Junichi; Kawashima, Susumu; Shiokawa, Masataka; Miyake, Hiroyuki; Yamazaki, Shunpei
Abstract : A 13.3‐inch 8k4k OLED display using an oxide semiconductor with high‐mobility IGZO material was fabricated. It was found that the use of a higher mobility material can decrease the size and power consumption of a gate driver. Furthermore, a stack of such oxide semiconductor layers can increase process stability.